Leukocyte responses to immobilized patterns of CXCL8 - Girrbach, Maria; Rink, Ina; Ladnorg, Tatjana; Azucena, Carlos; Heißler, Stefan; Haraszti, Tamás; Schepers, Ute; Schmitz, Katja (Colloids and surfaces. B, Biointerfaces, 2016)
The attachment of neutrophils to the endothelial surface and their migration towards the site of inflammation following chemokine gradients play an essential role in the innate immune response. Chemokines adhere to glycosaminoglycans on the endothelial surface to be detected by leukocytes and trigger their movement along surface- bound gradients in a process called haptotaxis. In assays to systematically study the response of leukocytes to surface-bound compounds both the spatial arrangement of the compound as well as the mode of immobilization need to be controlled. In this study microcontact printing was employed to create patterns of hydrophobic or functionalized thiols on gold-coated glass slides and CXCL8 was immobilized on the thiol coated areas using three different strategies. Human neutrophils adhered to the CXCL8-coated lines but not to the PEG-coated background. We could show that more cells adhered to CXCL8 adsorbed to hydrophobic octadecanethiol than on CXCL8 covalently bound to amino undecanethiol or CXCL8 specifically bound to immobilized heparin on aminothiol. Likewise general cell activity such as lamellipodia formation and random migration were most pronounced for CXCL8 adsorbed on a hydrophobic surface which may be attributed to the larger amounts of protein immobilized on this type of surface.
Gesehen am 12.06.2020